Amelioration of Immune Response Induced Cytokine Imbalance by MERS-CoV Antigen in Gallus gallus domesticus Model by Ethanolic Extract of Nymphaea caerulea - Chatterjee, Debasmita; Singh, Banhishikha; Paira, Krishnendu; Das, Satadal (Asian Journal of Biological and Life Sciences)
Background: Middle East Respiratory Syndrome Coronavirus (MERS-CoV) surfaced in late 2012 and was responsible for widespread infection and death throughout the globe. According to research reports, there is no potential medicine or vaccination available for the treatment or prevention of MERS-CoV. Aim: Therefore, in this particular study, we intended to explore the anti-viral activity of Nymphaea caerulea flower extract against MERS-CoV spike protein antigen-induced pathogenicity in fertilized egg model of Gallus gallus domesticus in terms of homeostasis of cytokine imbalance and morphological changes. Materials and Methods: Different experimental sets were prepared with 14th day fertilized chick eggs and they were aseptically harvested on the 16th day. Allantoic fluids were collected to study relative fold change in gene expression assay of targeted cytokines- Interferons (IFN) α, β, γ and Interleukins-IL-6, IL-8, IL-10, IL-1β concerning β actin. The ethanolic extract of N. caerulea was also scanned in the UV-vis range to identify the phytochemicals. Results: The well-known delayed stimulation of the IFN-α showing anti-viral activity following the MERS virus was found marginally improved by blue lotus extract. Moreover, the pro-inflammatory effect of cytokine IL-8 was found markedly suppressed by the blue lotus extract in the preventive set. Up-regulated IL-1β gene expression by MERS antigen was also significantly suppressed both in the curative and preventive sets. Conclusion: Thus, this novel study revealed many cytokine gene expression homeostasis by ethanolic extract of N. caerulea flower against MERS virus antigeninduced immune-pathogenic changes.
Keywords: Cytokines; Gallus gallus domesticus; Middle East respiratory syndrome corona virus; Nymphaea caerulea